(النفط العربي في الاستراتيجيات العالمية) - ديوب, محمد معن; شرف, سمير; محمد, فادي مالك (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعتبر الأمن الوطني- لدول العالم الصناعي- بشتى مجالاته الاقتصادية والاجتماعية والعسكرية مرتكزاً على الأمن النفطي، نتيجةً للارتباط الوثيق بين النفط من جهة، والاقتصاد والصناعة والنقل وفاعلية القوات المسلحة من جهة أخرى، ومن هنا كانت دول العالم وبالأخص الدول الصناعية الكبرى تسعى دائماً من أجل الحصول على النفط بانتظام وبكميات كافية وبأسعار تضمن النمو الاقتصادي الطبيعي. ويعني ذلك اتخاذ الإجراءات الكفيلة بضمان إمدادات النفط وإبقائها بعيدةً عن التهديد، وترتب على هذه الحماية الكبرى للنفط أن أصبح منذ نهاية الحرب العالمية الثانية جزءاً لا يتجزأ من العلاقات الدولية وأحد المتغيرات الكبرى التي تقوم بدور فاعل في صراع القوى العالمي. وانطلاقاً من المكان المرموق الذي يشغله النفط العربي في سلة النفط العالمية، وما يحمل من ميزات نسبية وأهمية استراتيجية. وجدنا أنه لا بد من وضع دراسة تتناول موقع النفط العربي في الاستراتيجيات العالمية، وما هي المزايا التي يتمتع بها هذا النفط عن غيره والتي تجعله متفوقاً من ناحية الاستثمار والجدوى الاقتصادية، إضافةً إلى إبراز حاجة العرب إلى نفطهم المهدد بالسلب والسيطرة الاستعمارية، وما هي أبرز الصراعات والمخططات المرسومة للسيطرة على نفط الخليج العربي. The national security of the world's industrial nations in its different fields whether economical, social or military, is considered to be based on oil, due to the strong connection between oil on the one hand, and economy, industry, transportation and efficiency of the armed forces on the other hand. That is why nations all over the world, specially the great industrial ones, always seek to get oil regularly and in sufficient amounts and by prices that insure the national economical growth. This means making procedures that insure continuous oil supply and keeping it away from threat. Since the end of the Second World War, the great protection of oil led it to be an integral part of the international relationships and one of the major variables that has an effective role in the struggle of the international powers. Starting from the important position of the Arabic oil in the "basket" of the international oil, and due to its proportional features and its strategic importance, we found that it is very important to make a study that deals with the position of Arabic oil among the international strategies and its advantages that make it superior in investment and economy, besides illustrating the need of the Arab to their oil, which is threatened by stealing and colonial dominance as well as the eminent struggle and plans that aim to control the oil of the Arabic Gulf.